Peran Musik Dalam Rangka Meningkatkan Keyboarding Skills - Raharso, Sri; Tjahjawati, Sri Surjani; Setiawardani, Maya (Jurnal Riset Bisnis dan Investasi, 2015)
The purpose of this research was to determine the role of music and genre of music that produces the fastest typing speeds in words per minute. Respondent of this research divided into two groups. The first group is a control group that learned keyboarding skill without music, the rest group learned keyboarding skill with music. The music that used in that experiments coming from Mavis Beacon Teaches Typing 26. The number of the word per minute for each respondent was recorded, three times, at the beginning, in the middle, and the end of the course; labeled by Kstart, Kmiddle, and Kend. In spite of identifying role of genre music to typing performance, the second group typed predetermined line while listening to different predetermined music. The genre categories uses were jazz, blues, rock, reggae, degung (Sundanese music), and classic. The number of words per minute for each respondent was recorded. Every respondent has three trials were run. The recorded information was compared. The result of this experiment showed that music played a significant role to shape typing performance. Second, this experiment showed that rock music produced the fastest typing speeds. Blues produced the second fastest typing speed. Jazz produces the third fastest typing speed.